Effects of ball drills and repeated-sprint-ability training in basketball players - Maggioni, M. A.; Bonato, M.; Stahn, A.; La Torre, A.; Agnello, L.; Vernillo, G.; Castagna, C.; Merati, G. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the effects of ball drills and repeated-sprint-ability training during the regular season in basketball players. Methods: A total of 30 players were randomized into 3 groups: ball-drills training (BDT, n = 12, 4 × 4 min, 3 vs 3 with 3-min passive recovery), repeated-sprint-ability training (RSAT, n = 9, 3 × 6 × 20-m shuttle running with 20-s and 4-min recovery), and general basketball training (n = 9, basketball technical/tactical exercises), as control group. Players were tested before and after 8 wk of training using the following tests: VO2max , squat jump, countermovement jump, Yo-Yo Intermittent Recovery Test Level 1 (YIRT1), agility T test, line-drill test, 5-/10-/20-m sprints, and blood lactate concentration. A custom-developed survey was used to analyze players' technical skills. Results: After training, significant improvements were seen in YIRT1 (BDT P = .014, effect size [ES] ± 90% CI = 0.8 ± 0.3; RSAT P = .022, ES ± 90% CI = 0.7 ± 0.3), the agility T test (BDT P = .018, ES ± 90% CI = 0.7 ± 0.5; RSAT P = .037, ES ± 90% CI = 0.7 ± 0.5), and the line-drill test (BDT P = .010, ES ± 90% CI = 0.3 ± 0.1; RSAT P < .0001, ES ± 90% CI = 0.4 ± 0.1). In the RSAT group, only 10-m sprint speeds (P = .039, ES ± 90% CI = 0.3 ± 0.2) and blood lactate concentration (P = .004, ES ± 90% CI = 0.8 ± 1.1) were improved. Finally, technical skills were increased in BDT regarding dribbling (P = .038, ES ± 90% CI = 0.8 ± 0.6), shooting (P = .036, ES ± 90% CI = 0.8 ± 0.8), passing (P = .034, ES ± 90% CI = 0.9 ± 0.3), rebounding (P = .023, ES ± 90% CI = 1.1 ± 0.3), defense (P = .042, ES ± 90% CI = 0.5 ± 0.5), and offense (P = .044, ES ± 90% CI = 0.4 ± 0.4) skills. Conclusions: BDT and RSAT are both effective in improving the physical performance of basketball players. BDT had also a positive impact on technical skills. Basketball strength and conditioning professionals should include BDT as a routine tool to improve technical skills and physical performance simultaneously throughout the regular training season.